2019
DOI: 10.1002/jsfa.9513
|View full text |Cite
|
Sign up to set email alerts
|

Tracing individuals and populations of the tambaqui, Colossoma macropomum (Cuvier, 1818), from Brazilian hatcheries using microsatellite markers

Abstract: BACKGROUND In recent years, tracing of alimentary produce of animal origin has become increasingly important, for economic, food safety and ecological reasons. The tambaqui, Colossoma macropomum, is the native fish most farmed in Brazil. The reliable identification of the origin of tambaquis (wild or farmed) offered for sale to the general public has become necessary to satisfy regulatory norms and uphold consumer confidence. Molecular methods based on the analysis of DNA sequences have often been used to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(116 reference statements)
1
1
0
1
Order By: Relevance
“…For the A. gigas , identification at the population level had better performance than the individual discrimination, which corroborates the findings of [ 11 , 28 ]. A simulation study reported that at least 15 microsatellites are necessary to correctly reach 95% of confidence in attribution decisions [ 48 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For the A. gigas , identification at the population level had better performance than the individual discrimination, which corroborates the findings of [ 11 , 28 ]. A simulation study reported that at least 15 microsatellites are necessary to correctly reach 95% of confidence in attribution decisions [ 48 ].…”
Section: Discussionsupporting
confidence: 88%
“…At the individual level, the process is based on parental screening for the identification of individuals. At the population level, it is based on identifying allelic frequencies using probabilistic or deterministic approaches [ 11 ]. For the A. gigas , the genetic tracing can be useful against the illegal trade through genetic proof of the origin of the marketed animals, and it could also help in the implantation of breeding genetic management in the aquaculture farms based on the identification of DNA profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Apesar da tecnologia CRISPR ainda não ter sido aplicada às espécies amazônicas, recentemente estudos envolvendo biologia molecular têm sido cada vez mais explorados e a principal espécie-alvo é C. macropomum. Entre as técnicas mais utilizadas estão o uso de marcadores microssatélites para identificar a origem dos animais 39 , análise de transcriptoma para avaliação da expressão gênica 40; 41 , uso de marcadores moleculares para identificação de células-tronco 42; 43 e a identificação de microRNAs 44 . Outras espécies amazônicas também têm sido alvo de estudos envolvendo microssatélites 45 , filogenia e caracterização molecular de parasitas 46; 47; 48 e estudo de genes mitocondriais para análise de relações taxonômicas e evolutivas 49 .…”
Section: Biotecnologias Aplicadas à Reproduçãounclassified